"DEVELOPING COMMUNICATIVE COMPETENCE IN MEDICAL STUDENTS THROUGH 'DOCTOR-PATIENT' CASE STUDIES IN ESP CLASSROOMS" (Ustozlar uchun, 2026)
The modernization of medical education in Uzbekistan necessitates a transition toward competency-based language instruction. This article explores the efficacy of using "Doctor-Patient" case studies to enhance the communicative competence of medical students within the English for Specific Purposes (ESP) framework. In light of recent national reforms, including Presidential Decrees aimed at internationalizing healthcare, the ability to communicate professionally in English has become a core clinical requirement. The study analyzes a tri-phase methodological model—comprising linguistic scaffolding, active simulation, and reflexive feedback—to demonstrate how simulated clinical encounters bridge the gap between academic knowledge and practical bedside manners. By integrating digital tools and international assessment standards like OSCE, this approach not only improves linguistic accuracy but also fosters essential soft skills such as empathy and ethical discourse.